Extensional flow-induced conductive nanohybrid shish in poly(lactic acid) nanocomposites toward pioneering combination of high electrical conductivity, strength, and ductility. (15th February 2021) - Xue, Bai; Cheng, Ziling; Yang, Shengdu; Sun, Xin; Xie, Lan; Zheng, Qiang
Abstract: Balanced electrical conductivity and mechanical properties are always of great significance for the practical applications of conductive polymer composites (CPCs), especially for the inherent brittle poly(lactic acid) (PLA)-based CPCs. Herein, the phase control methodology (i.e. carbon nanotubes (CNTs) and intense extensional flow field synergistically induced PLA crystallization) was proposed to achieve the in situ electrically conductive nanohybrid shish that is composed of plenty of CNTs coated by PLA crystalline phase. In addition, the conductive networks were easily constructed by the combined effect of 1 D wire-like conductive nanohybrid shish and 2 D patch board-like graphene (GE) for highly conductive PLA/CNT/GE nanocomposites. Compared with common pure PLA (4.2 × 10 −12 S/cm), the electrical conductivity of PLA/CNT5/GE0.1 (1.32 S/cm) was sharply increased by 12 orders of magnitude. Meanwhile, due to the strong reinforcing effects of nanohybrid shish, PLA/CNT5/GE0.1 exhibited unexpectedly simultaneous enhancement in ductility, strength, and stiffness, outperforming common pure PLA with increase of 1952%, 40.6%, and 24.1%, respectively. Of particular interest was the conductive nanohybrid shish fabricated with industrial feasibility, displaying the competitive advantages in achieving high-conductivity and high-performance PLA, even for other semicrystalline polymers. The unprecedented combination of high electrical conductivity, ductility, strength, and stiffness established in PLA-based nanocomposites only by tailoring the crystalline microstructures is in great potential need for electromagnetic shielding, electronic devices, and antistatic packaging applications. Graphical abstract: Image 1 Highlights: Conductive nanohybrid shish was fabricated under intense extensional flow field. The synergetic effect of nanohybrid shish and graphene enhanced the conductivity. Nanohybrid shish exhibited the strong reinforcing effect in PLA nanocomposites. High conductivity, strength, and ductility of PLA/CNT/GE were achieved.